2019
DOI: 10.3390/geosciences9080346
|View full text |Cite
|
Sign up to set email alerts
|

Warm Deep Water Variability During the Last Millennium in the CESM–LME: Pre-Industrial Scenario versus Late 20th Century Changes

Abstract: Water transformation around Antarctica is recognized to significantly impact the climate. It is where the linkage between the upper and lower limbs of the Meridional Overturning Circulation (MOC) takes place by means of dense water formation, which may be affected by rapid climate change. Simulation results from the Community Earth System Model Last Millennium Ensemble (CESM–LME) are used to investigate the Weddell Sea Warm Deep Water (WDW) evolution during the Last Millennium (LM). The WDW is the primary heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
(165 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have shown a shoaling and warming trend of WDW since 1990's, although it has experienced some periods of cooling (Robertson et al, 2002;Fahrbach et al, 2004Fahrbach et al, , 2011. This pattern in the WDW has also been reproduced by climate models (Tonelli et al, 2019). In our study, climatologies (Figure 4 c and d) show that the intermediate layer temperature is on average within the range of observations for the WDW (Whitworth et al, 1998;Orsi et al, 1993;Robertson et al, 2002).…”
Section: External Forcings E↵ects On the Hydrographic Fieldssupporting
confidence: 88%
“…Previous studies have shown a shoaling and warming trend of WDW since 1990's, although it has experienced some periods of cooling (Robertson et al, 2002;Fahrbach et al, 2004Fahrbach et al, , 2011. This pattern in the WDW has also been reproduced by climate models (Tonelli et al, 2019). In our study, climatologies (Figure 4 c and d) show that the intermediate layer temperature is on average within the range of observations for the WDW (Whitworth et al, 1998;Orsi et al, 1993;Robertson et al, 2002).…”
Section: External Forcings E↵ects On the Hydrographic Fieldssupporting
confidence: 88%
“…Significant increases in SST are not expected to happen in the northwestern Antarctic Peninsula (NWAP) coast before 2080 nor until the end of the century in the northwestern Weddell Sea (NWWS; Figure 2A). This is particularly relevant to reassure the Weddell Sea (WS) ability to cushion the offshore warming signal advected by the Weddell Gyre (Ryan et al, 2016) due to the local dynamics and cryosphere-related processes (Fahrbach et al, 2011;Tonelli et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These human-induced changes have already spread to about half (20-55%) of the world oceans (Silvy et al, 2020), and the largest heat gain has occurred in the Southern Ocean (Roemmich et al, 2015;Trenberth et al, 2016). However, the ice-insulated regions of the SO protect its sea surface waters from climate forcing (Gille, 2008(Gille, , 2002Fahrbach et al, 2011;Tonelli et al, 2019). As a result, heat and carbon uptake happens mostly through the formation and subduction of water masses (Heuzé et al, 2013;Sallée et al, 2013), and the earliest detection of the anthropogenic warming fingerprint in the SO occurs in the ocean interior rather than in surface waters (Silvy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation